The Impact of The Development of the Lasiana Beach Tourism Area on the Community Economy and Government Revenue (PAD) - Jeni J. Therik (Journal of Social Research, 2023)
Lasiana Beach is one of the tourist attractions located in Kupang City which is a tourist destination for the people of Kupang City and its surroundings. This research aims to determine the economic impact of developing the Lasiana Beach tourist area for the community and government (PAD). This research was conducted at the NTT Province Tourism and Creative Economy Service. This research is a qualitative descriptive research with data collection methods through interviews and observations while the informants are government officials and people who do business in the area and visitors. The focus of the research is the economic impact in the form of community income, employment opportunities, and government income (PAD). The research results show that the income earned by people who do business in the area every day is still low. There are job opportunities for the community by opening businesses in the area but these business opportunities have not been utilized properly and there is income generated for the government in the form of levies but this has not yet met the target. This is due to the low number of visitors visiting Lasiana Beach.